INFLUENCE OF SOCIAL MEDIA ON CUSTOMER ENGAGEMENT AND PERCEPTION AT RETRO COFFEE HOUSE PH IN NOVALICHES QUEZON CITY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Social media has become an indispensable tool for businesses in the hospitality industry, boosting brand visibility and fostering active customer engagement. Through these platforms, hotels and restaurants can effectively showcase their offerings, respond promptly to inquiries, and build personal connections that enhance trust and loyalty. User-generated content and influencer collaborations further strengthen credibility and expand marketing reach. However, challenges such as misinformation and inconsistent branding can harm public perception, making it crucial for businesses to maintain a consistent voice and address concerns swiftly. This study employed a quantitative research design to examine the influence of social media on customer engagement and perception at Retro House Coffee PH in Novaliches, Quezon City. By collecting numerical data and utilizing statistical analysis, the approach aimed to ensure validity and reliability. The sample consisted of 100 customers, with a gender distribution of 35% male and 65% female, indicating a higher female representation. Purposive sampling was used to select participants based on relevant characteristics. Data collection was conducted through a self-designed questionnaire, developed using Parasuraman’s customer satisfaction framework. The study revealed that the majority of respondents at Retro House Coffee PH are young adults between 18 and 27 years old, with males slightly outnumbering females. Most participants are single and visit the café infrequently, mainly interacting with the brand via Facebook. The café’s social media marketing efforts, including well-crafted content and targeted advertising, are viewed positively and contribute significantly to increased brand loyalty, purchase intentions, customer perception, and trust. Of the demographic variables examined, only civil status demonstrated a meaningful correlation with social media engagement. Nonetheless, issues such as slow response times and inaccurate information were noted as obstacles to effective customer interaction. It is recommended to introduce exclusive in-store promotions to increase offline visits, improve response times through the use of chatbots, tailor content to suit various demographic segments, encourage user-generated content to boost brand loyalty, and optimize social media navigation for enhanced accessibility.
Keywords: social media marketing; customer engagement; brand loyalty; retro house coffee ph; quantitative research; customer perception; user-generated content; chatbots; demographic targeting; in-store promotions